Moving the line of scrimmage : masculinity in Richard Ford - Gushue, Marc William, 1972- (2000)
Thesis (M.A.)--Memorial University of Newfoundland, 2001. English Language and Literature Bibliography: leaves [128-138] Novelist Richard Ford has created the first important character of the masculinist age of American fiction: Frank Bascombe. In The Sportswriter and Independence Day Frank is an Everyman who faces the issues commonly confronted by men in contemporary American society: issues such as raising children, divorce, mid-life crisis, relationships with women, relationships with men, and professional life. -- In my thesis I argue that what has been called the "masculine mystique" is the central antagonist in both novels by Ford- The term is borrowed from the newly-emerged field of men's studies, and refers to codes of conduct that are imprinted on boys by society. Using theorists from this controversial field such as Brod, Pleck, and Messner, I explore the men's studies stance on gender socialization, and demonstrate the ways in which Ford's novels contribute to that debate. -- Men's studies seeks to bring a subjective perspective to men's lives-a perspective that heretofore has not been central in the criticism of fiction. I investigate the value of this perspective and demonstrate the ways in which Ford's novels are illustrative of the male condition in postmodern USA.